Field and synthetic experiments for virtual source crosswell tomography in vertical wells: Perth Basin, Western Australia - Almalki, Majed; Harris, Brett; Dupuis, C. (Elsevier, 2013)
It is common for at least one monitoring well to be located proximally to a production well. This presents the possibility of applying crosswell technologies to resolve a range of earth properties between the wells. We present both field and synthetic examples of dual well walk-away vertical seismic profiling in vertical wells and show how the direct arrivals from a virtual source may be used to create velocity images between the wells. The synthetic experiments highlight the potential of virtual source crosswell tomography where large numbers of closely spaced receivers can be deployed in multiple wells. The field experiment is completed in two monitoring wells at an aquifer storage and recovery site near Perth, Western Australia. For this site, the crosswell velocity distribution recovered from inversion of travel times between in-hole virtual sources and receivers is highly consistent with what is expected from sonic logging and detailed zero-offset vertical seismic profiling. When compared to conventional walkaway vertical seismic profiling, the only additional effort required to complete dual-well walkaway vertical seismic profiling is the deployment of seismic sensors in the second well. The significant advantage of virtual source crosswell tomography is realised where strong near surface heterogeneity results in large travel time statics.